Characteristics and determinants of the labor market of jurisconsults in Colombia (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
The article presents some of the results achieved, achieved and pending of the research project on the labor market of the legal advisor. Its objective is to reverse the generalized idea related to the abundance of students and graduates of Law when talking about a formation of which little is known about its composition, structure and labor parameters above the usual ones to the administration of justice, the rule of law and litigation; all this in a career that, like few others, enjoys a wide labor field in different scientific, interdisciplinary, technical and transdisciplinary fields. The methodology conceived in the exploratory and descriptive methods showed that the labor market of judicial counselors has been little studied. Meanwhile, the methodology from the school of neoclassical analysis of markets by economics shows that studies on the markets of judicial counselors are practically non-existent, left to the sway of speculations or expectations. In line with what has been worked on, the possible method for evaluating the markets of judicial counselors is presented, followed by the results achieved and attained; the elements of discussion and debate; the conclusions and the possible basic references in which it is suggested to carry out studies on this labor market.
Keywords: economy; jurisconsults; markets; methodica; neoclassical